Social media experiences of adolescents and young adults with cerebral palsy who use augmentative and alternative communication. (2nd January 2017) - Caron, Jessica Gosnell; Light, Janice
Abstract: Purpose : This pilot study aimed to expand the current understanding of how adolescents and young adults with cerebral palsy (CP) and complex communication needs use social media. Method : An online focus group was used to investigate the social media experiences of seven individuals with CP who used Augmentative and Alternative Communication (AAC). Questions posed to the group related to social media: (a) advantages; (b) disadvantages; (c) barriers; (d) supports; and (e) recommendations. Result : Adolescents with CP who use AAC used a range of communication media to participate in daily interactions, including social media. An analysis of the focus group interaction revealed that the participants used social media to: bypass the constraints of face-to-face interactions; communicate for a number of reasons (e.g. maintain relationships, share experiences); and support independent leisure (e.g. playing games, looking at pictures/videos). Despite the advantages, the participants discussed barriers including limitations related to AAC technologies, social media sites and literacy skills. Conclusion : The results suggest that service providers should implement interventions to support social media use, including enhancement of linguistic, operational and strategic competence. Technology manufacturers should focus on improving the designs of AAC apps and social media sites to facilitate access by individuals who require AAC.